FACTORS INFLUENCING CONSUMER LOYALTY THROUGH THE MEDIATION OF CONSUMER SATISFACTION IN MARJAN SYRUP - Assabila, Masya Dinia; Relawati, Rahayu; Ningsih, Gumoyo Mumpuni Ningsih (Jurnal Hexagro, 2026)
The success of the Marjan syrup company has led to the emergence of several new brands, creating new competitors for Marjan syrup. This has led to the emergence of new threats that businesspeople must face. Efforts to maintain products on the market must build a loyal consumer base. This study seeks to identify factors influencing consumer loyalty to Marjan syrup in Gresik, with product quality, price, and promotion as variables, and consumer satisfaction as the mediating variable. The sampling technique uses accidental sampling. Determination: The sampling quota for this study was 85 people from Marjan syrup consumers in the city of Gresik. The analytical method used is Structural Equation Modeling with the Partial Least Squares (PLS) approach. The results indicate that product quality and promotion have a positive and significant impact on consumer loyalty, mediated by Marjan syrup consumer satisfaction. Consumer satisfaction has a significant influence on consumer loyalty to Marjan syrup, with an Original Sample value of 0.929. Price has a good but not significant impact on consumer satisfaction. The latent variable with the greatest impact on this research is the consumer satisfaction variable, with a t statistic of 55,627, the highest value, and the P-value closest to 0. This means that the consumer satisfaction variable has a big impact on consumer loyalty for Marjan syrup in Gresik. Keywords: Consumer Loyalty, Consumer Satisfaction, Price, Product Quality, Promotion